1988
DOI: 10.1051/alr:1988024
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition and energy value ofCrassostrea gigas(Thunberg) cultured in the bay of Marennes-Oléron

Abstract: In the bay of Marennes-Oléron the dry flesh of Crassostrea gigas ranged from 29 to 52% proteins, 10 to 23% ash, 6 to 20% lipids and O to 4% carbohydrates of which 48.3*21.6% were glywgen. The energy value ranged frorn 18.84 to 23.47 joule. mg-' ash free dry weight (rnean 20.27 J. mg-'). Reproductive effort varied from 17.8 to 55.9% dry weight for males, and 43.1 to 61.9% for females during the first and third year of reproduction respectivcly. A high energy value for female gametes (23.47 to 26.24 J.mg-' dry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 18 publications
5
45
1
4
Order By: Relevance
“…This may be because the presence of M. orientalis in quantity in the intestinal tract of molluscs can interrupt the intestinal transit and cause an alimentary spoilation (His 1977). This spoilation is thought to induce a decrease of energetic reserves, constituted mainly by glycogen (Deslous-Paoli & Heral 1988). A loss of glycogen was not found in the present study; however, many studies find that parasites have a noticeable impact on the host only in times of low food availability and other stresses (Hepper 1955, His 1977.…”
Section: Discussioncontrasting
confidence: 56%
“…This may be because the presence of M. orientalis in quantity in the intestinal tract of molluscs can interrupt the intestinal transit and cause an alimentary spoilation (His 1977). This spoilation is thought to induce a decrease of energetic reserves, constituted mainly by glycogen (Deslous-Paoli & Heral 1988). A loss of glycogen was not found in the present study; however, many studies find that parasites have a noticeable impact on the host only in times of low food availability and other stresses (Hepper 1955, His 1977.…”
Section: Discussioncontrasting
confidence: 56%
“…Cáceres-Martinez & Figueras (1998) also found no difference in gonad development of the mussel Mytilus galloprovincialis between 2 and 5 m depths. Deslous-Paoli & Heral (1988) demonstrated that seasonal variations in reproductive condition and biochemical composition of the oyster Crassostrea gigas could be affected by cultivation density (i.e. relative food availability), in addition to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…On the European Atlantic coast, it has spread further to the Netherlands and Ireland (Stock 1993;Holmes and Minchin 1995) and has also been introduced with C. gigas into the Mediterranean Sea (Clantzig 1989). Although it was initially feared that M. orientalis could initiate an epidemic similar to the one assumed with M. intestinalis in 1949-1951, this has not yet been observed, and harm to the host C. gigas seems to be small (Deslous-Paoli and Héral 1988;De Grave et al 1995;Steele and Mulcahy 2001).…”
Section: Introductionmentioning
confidence: 99%